A holistic framework for the development of a sustainable touristic model. (2015) - Alkier, Romina; Milojica, Vedran; Roblek, Vasja
This article reflects on confronting Western Balkans countries with the sustainable development. The goal of this paper is to present the importance of the development of the concept of the ST model and its role in economic and social development of rural areas of the Western Balkans. The purpose of the model is to find out how ST can contribute to the development of rural areas and economic growth in the Western Balkans, and to provide an answer to the research question: which areas of development processes and operations, and their aspects, are essential for the development of ST in the Western Balkans.